2020
DOI: 10.1002/aoc.5976
|View full text |Cite
|
Sign up to set email alerts
|

Isoxazole derivatives of silatrane: synthesis, characterization, in silico ADME profile, prediction of potential pharmacological activity and evaluation of antimicrobial action

Abstract: A new family of mono‐ (3a‐h) and bis‐ (4a‐g) isoxazole‐bridged silatranes has been synthesized by the reaction of 3‐aminopropylsilatrane (1) and 3‐substituted 5‐chloro‐methylisoxazoles (2a‐h). The structure of the isoxazole‐silatrane hybrids is characterized by elemental analysis, FT‐IR, UV, NMR (1H, 13C,29Si and 15N) spectroscopy, high‐resolution mass spectrometry, and X‐ray diffraction analysis. The in silico ADME (absorption, distribution, metabolism, excretion) assessment reveals that properties of mono‐ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 44 publications
0
13
0
2
Order By: Relevance
“…When compared to the conventional medicine gentamicin (MIC 25 and 50 μg/mL), Silatrane 3 with R = 4-MeOC 6 H 4 had a lower minimum inhibitory concentration (MIC 12. S C H E M E 5 6 Synthesis of a novel class of mono-and bisisoxazole-linked silatranes [76] L. Donovani [78]. In comparison with Miltefosine, the standard drug used in bioassays, some of the derivatives exhibited curiously improved inhibition of promastigote and amastigote stages of parasites.…”
Section: Other Synthetic Routesmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to the conventional medicine gentamicin (MIC 25 and 50 μg/mL), Silatrane 3 with R = 4-MeOC 6 H 4 had a lower minimum inhibitory concentration (MIC 12. S C H E M E 5 6 Synthesis of a novel class of mono-and bisisoxazole-linked silatranes [76] L. Donovani [78]. In comparison with Miltefosine, the standard drug used in bioassays, some of the derivatives exhibited curiously improved inhibition of promastigote and amastigote stages of parasites.…”
Section: Other Synthetic Routesmentioning
confidence: 99%
“…The interaction of 3‐aminopropylsilatrane 1 and 3‐substituted 5‐chloro‐methylisoxazoles 2 yielded a novel class of mono‐ isoxazole‐linked silatranes 3 and bis‐isoxazole‐linked silatranes 4 as depicted in the Scheme 56 [76]. Preliminary antimicrobial activity testing of the produced silatranes against Enterococcus durans, Bacillus subtilis, E. coli , and Pseudomonas aeruginosa suggests that all tested samples are only active against gram‐positive bacteria.…”
Section: Biological Activities Of Isoxazole Derivativesmentioning
confidence: 99%
“…A series of novel organic–inorganic hybrids, combining one ( 16 ) or two ( 17 ) units of the isoxazole motif and one silatrane unit in a single molecule, were synthesized ( Figure 5 ) [ 51 ]. The screening of silatranes ( 16 ) and ( 17 ) for antimicrobial activity against Enterococcus durans , Bacillus subtilis , Escherichia coli , and Pseudomonas aeruginosa revealed that all the test samples were active only against Gram-positive microorganisms.…”
Section: Silatranyl Physiologically Active Compoundsmentioning
confidence: 99%
“…В Иркутском институте химии СО РАН получен широкий ряд синтетических биологически активных соединений, названных «атраны» [11][12][13], в частности ряд арил-халькогенилацетатов трис(2-гидроксиэтил)аммония, названный «протатраны», с общей формулой ArХCH 2 CO 2 -• НN + (CH 2 СН 2 ОН) 3 (А), где Ar = арил; Х = S, SO, SO 2 , Se [14].…”
Section: финансированиеunclassified